2022
DOI: 10.3389/fonc.2022.1054086
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-immune-endocrine mechanisms with poor adherence to aromatase inhibitor therapy in breast cancer

Abstract: As the most commonly used endocrine therapy regimen for patients with hormone receptor-positive (HR+) breast cancer (BC) at present, aromatase inhibitors (AIs) reduce the risk of localized and distant recurrence, contralateral BC and secondary cancer, and prolong disease-free survival. Clinical data show that poor adherence during AI treatment is mainly attributed to muscle and joint pain, fatigue, anxiety, depression and sleep disturbances during treatment. The rapid decline of estrogen caused by AIs in a sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“… 1 Recent studies have shown that in addition to suppressing estrogen production and signaling, these agents can enhance the production of inflammatory cytokines, induce dysregulation of activities of circulating immune cells, including natural killer (NK) cells, 2 - 7 and boost immune responses. 8 - 10 By disrupting neuro-immune-endocrine (NIE) networks, 11 , 12 ET may contribute to fatigue, 13 sleep disruption, 14 and inflammation around the joints and muscles, 15 leading to impaired quality of life (QoL) and affecting treatment adherence. 16 As nonadherence to adjuvant ET is correlated with impaired cancer-specific survival, 17 proper management of these adverse effects is vital for improving the health outcomes of BC survivors.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Recent studies have shown that in addition to suppressing estrogen production and signaling, these agents can enhance the production of inflammatory cytokines, induce dysregulation of activities of circulating immune cells, including natural killer (NK) cells, 2 - 7 and boost immune responses. 8 - 10 By disrupting neuro-immune-endocrine (NIE) networks, 11 , 12 ET may contribute to fatigue, 13 sleep disruption, 14 and inflammation around the joints and muscles, 15 leading to impaired quality of life (QoL) and affecting treatment adherence. 16 As nonadherence to adjuvant ET is correlated with impaired cancer-specific survival, 17 proper management of these adverse effects is vital for improving the health outcomes of BC survivors.…”
Section: Introductionmentioning
confidence: 99%